An efficient approach to address issues of graphene nanoplatelets (GNPs) incorporation in aluminium powders and their compaction behaviour - Baig, Z. (MDPI AG, 2018)
The exceptional potential of the graphene has not been yet fully translated into the Al matrix to achieve high-performance Al nanocomposite. This is due to some critical issues faced by graphene during its processing such as the dispersion uniformity, structure damage, compatibility/wettability, and low graphene embedding content in Al matrix. In the present work, a new integrative method was adopted and named as âsolvent dispersion and ball millingâ (SDBM) to address the issues above efficiently in a single approach. This strategy involves effective graphene nanoplatelets (GNPs) solvent dispersion via surfactant decoration and solution ball milling employed to polyvinyl alcohol (PVA) coated Al with various GNPs content (0.5, 1 and 1.5 wt. ). Flaky Al powder morphology attained by optimizing ball milling parameters and used for further processing with GNPs. Detailed powders characterizations were conducted to investigate morphology, graphene dispersion, group functionalities by FTIR (Fourier transform infrared spectroscopy) spectroscopy and crystallinity by powder XRD (X-ray diffraction)analysis. Compaction behaviour and spring back effect of the GNPs/Al powders was also investigated at different compaction pressure (300 to 600 Mpa) and varying GNPs fractions. In response, green and sintered relative density () along with effect on the hardness of the nanocomposites samples were examined. Conclusively, in comparison with the unreinforced Al, GNP/Al nanocomposite with 1.5 wt. GNPs exhibited the highest hardness gives 62 maximum increase than pure Al validates the effectiveness of the approach produces high fraction uniformly dispersed GNPs in Al matrix. Â© 2018 by the authors. Licensee MDPI, Basel, Switzerland.